Cerebral microbleeds in Down syndrome: association with demographic, genetic, fluid and imaging biomarkers of Alzheimer’s disease - Zsadanyi, Sara E.; Morcillo‐Nieto, Alejandra O.; Aranha, Mateus Rozalem; Aragón, Irina; Montal, Victor; Pegueroles, Jordi; Vaqué‐Alcázar, Lídia; Benejam, Bessy; Videla, Laura; Barroeta, Isabel; Fernandez, Susana; Giménez, Sandra; et al. (Alzheimer's & dementia, 2023)
Background With the development of amyloid‐modifying therapeutic agents that can lead to cerebral microhaemorrhages, it is critical to meticulously characterise the natural history of cerebral microbleeds (MBs) in populations genetically predisposed to develop Alzheimer’s disease (AD), such as Down syndrome (DS). We aimed to investigate MB prevalence in a large cohort of adults with DS and define associations with demographic, genetic, fluid and imaging biomarkers of AD, and cognitive performance. Methods Cross‐sectional design. Adults with DS and euploid controls from the Down Alzheimer Barcelona Neuroimaging Initiative underwent a 3T‐MRI protocol, including susceptibility‐weighted imaging (SWI) acquisition. Manual tracing of MBs was performed by two independent raters using ITK‐SNAP. Participants were classified according to MB status (MB‐/MB+) and severity (0, 1, 2+ MBs). Non‐parametric statistical tests were used to assess the effect of MBs on demographic, clinical, genetic, CSF and neuroimaging AD biomarkers, and cognitive tests. Results We included 247 participants with DS along the AD continuum, and 167 euploid controls (Table 1). The proportion of MB+ was higher in DS participants than controls, and progressively increased with AD clinical stages and age in the DS group (Fig. 1). By contrast, MB status did not differ by APOEε4 status, intellectual disability, or sex. In DS, the MB+ group had increased white matter hyperintensity volume and decreased hippocampal volumes compared to MB‐. DS MB+ also had lower CSF Aβ42/40 ratio, higher CSF t‐tau and p‐tau‐181 concentrations, and tended toward worse cognitive performance. Most effects gradually evolved with MB severity, although significant differences were mainly between MB‐ vs MB 2+ (Fig. 2). Finally, sensitivity analyses showed that most results became non‐significant when comparing DS MB+ to a 1:1 DS MB‐ group matched for age, sex, intellectual disability and/or AD diagnosis. Conclusion MB presence and severity are increased in adults with DS, and worsen with clinical progression and AD pathology. Yet, matched group analyses suggest that MB have limited impact on cognition and neurodegeneration. These results provide better characterisation of the presence and effect of MB in a population with an ultra‐high risk of developing AD who could benefit from new disease modifying drugs.